2006
DOI: 10.1111/j.1532-849x.2006.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disinfectants on the Hardness and Roughness of Reline Acrylic Resins

Abstract: The disinfectant solutions, 1% sodium hypochlorite and 4% chlorhexidine gluconate, caused no apparent damage on hardness and roughness of the materials evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
2
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 38 publications
7
56
2
10
Order By: Relevance
“…However, in water and 0.12% chlorhexidine digluconate there was a difference related to the increased microhardness, evidencing the results found by Azevedo et al 18 , who observed increased hardness of resin Duraliner II (self-polymerized reline resin) when immersed in 4% chlorhexidine digluconate and 1% sodium hypochlorite solutions for 7 days, relating the phenomena occurred to a higher polymerization and release of residual monomer present in the reaction, what may have overcame the plastifying effect of water absorption. Machado et al 12 ruled out the hypothesis that the disinfection of complete denture base with sodium perborate may change hardness properties of denture base and reline materials, since the increased hardness seen for resins Kooliner and Duraliner II may have occurred because of the presence of a certain amount of residual monomer during disinfection procedures.…”
Section: Discussionsupporting
confidence: 75%
“…However, in water and 0.12% chlorhexidine digluconate there was a difference related to the increased microhardness, evidencing the results found by Azevedo et al 18 , who observed increased hardness of resin Duraliner II (self-polymerized reline resin) when immersed in 4% chlorhexidine digluconate and 1% sodium hypochlorite solutions for 7 days, relating the phenomena occurred to a higher polymerization and release of residual monomer present in the reaction, what may have overcame the plastifying effect of water absorption. Machado et al 12 ruled out the hypothesis that the disinfection of complete denture base with sodium perborate may change hardness properties of denture base and reline materials, since the increased hardness seen for resins Kooliner and Duraliner II may have occurred because of the presence of a certain amount of residual monomer during disinfection procedures.…”
Section: Discussionsupporting
confidence: 75%
“…4,[13][14][15] Thus, many studies have been performed with the objective of evaluating the efficiency of different disinfecting solutions in the control of Candida genus yeasts, searching for a disinfecting solution that would present excellent antimicrobial activity without harming the patient's health or causing alterations in the physical-structural characteristics of dentures. [16][17][18][19][20] Within this context, the objective of the present study was to evaluate the effect of sodium bicarbonate in the adherence of Candida albicans to thermally activated acrylic resin, comparing it to other disinfecting solutions already mentioned and tested in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, few of the most commonly used disinfectants such as sodium hypochlorite; glutaraldehyde, chlorhexidine and sodium perborate [3,[15][16][17][25][26][27][28][29] were used in present study. The micro-organisms namely Streptococcus mutans and Candida albicans were studied since they are common commensals of oral cavity.…”
Section: Resultsmentioning
confidence: 99%